Sanitary and hygienic regulations in Ancient civilizations - Hotsuliak, Svitlana (Global Prosperity, 2022)
The article examines sanitary and epidemiological legislation in ancient civilizations on the basis of the analysis of the extant statutory acts of King Hammurabi and the Laws of Manu. By means of comprehensive study and analysis of the information base, the formation of sanitary-hygienic norms in ancient civilizations has been revealed. Despite a certain specificity of the scientific search, the theme of the article is very relevant, because the selection of methods for the implementation of historical and legal research of any orientation is concerned. The study of the methods used in the examination of sanitary and epidemiological laws in their system also serves to fulfil the historico-legal methodology’s low important functions: a) to identify ways of acquiring scientific knowledge, which reflect the dynamics of state-legal phenomena and processes; b) to ensure the universality of obtaining information on the state-legal process or the phenomenon under study. Thus, analyzing sanitary-hygienic regulations can be seen the origin of sanitary-hygienic norms, designed to ensure the preservation of public health. Indeed, in ancient times, great attention was paid to the prevention and precaution of epidemic diseases. In general, of course, it is hardly possible to establish exactly when the first diseases, much less epidemics, appeared among the population of our planet. The formation of sanitary-hygienic regulations in ancient civilizations was a complex and multifaceted phenomenon.